2016
DOI: 10.1002/ehf2.12088
|View full text |Cite
|
Sign up to set email alerts
|

Randomized pilot trial comparing tolvaptan with furosemide on renal and neurohumoral effects in acute heart failure

Abstract: AimsLoop diuretics are first‐line medications for congestive heart failure (CHF); however, they are associated with serious adverse effects, including decreased renal function, and sympathetic nervous and renin–angiotensin system activation. We tested whether tolvaptan, a vasopressin V2‐receptor antagonist, could reduce unfavourable furosemide‐induced effects during CHF treatment.Methods and resultsSixty patients emergently hospitalized owing to CHF‐induced dyspnea were randomly assigned to receive either 40 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
90
1
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(108 citation statements)
references
References 51 publications
(84 reference statements)
6
90
1
2
Order By: Relevance
“…Previous studies of TLV use were tested in acute HF without accounting for diuretic resistance. [8][9][10][11] There are 3 main findings of the present study. First, additive TLV resulted in significantly higher UV than increased FUR, primarily through increased urinary water excretion in HF patients with residual congestion despite concomitant FUR.…”
Section: Discussionmentioning
confidence: 51%
“…Previous studies of TLV use were tested in acute HF without accounting for diuretic resistance. [8][9][10][11] There are 3 main findings of the present study. First, additive TLV resulted in significantly higher UV than increased FUR, primarily through increased urinary water excretion in HF patients with residual congestion despite concomitant FUR.…”
Section: Discussionmentioning
confidence: 51%
“…Furthermore, in the study by Jujo et al, in which the effects of oral tolvaptan and intravenous furosemide on renal response were directly compared in ADHF patients, the WRF rate was significantly lower in HFpEF patients treated with tolvaptan than in HFpEF patients treated with furosemide, although the subgroup of HFpEF patients was not prospectively defined. 33 Although we observed an increased risk of WRF in ADHF patients treated with conventional diuretic therapy, there might be transient WRF during the acute phase that is not necessarily associated with a worse prognosis. 34 According to recent reports, transient WRF seems to provide some prognostic information in ADHF, 7 but its effect seems to be less than that of persistent WRF.…”
Section: Discussionmentioning
confidence: 52%
“…4) Our recent pharmacokinetic and pharmacodynamic studies have reported the effectiveness and safety of add-on tolvaptan to furosemide in HF patients with advanced kidney dysfunction. 5,6) As compared with furosemide, tolvaptan in patients with acute HF is associated with comparable decongestion, better preservation of renal function, and less activation of the RAAS; 7) however, the efficacy of tolvaptan with or without ARB/ACE-I therapy in hospitalized patients with acute decompensated HF has not been fully investigated. The most recently published study of Adachi, et al 8) suggested that a single use of tolvaptan might induce an increase in urine volume in acute decompensated HF patients who were not previously treated with ARB/ACE-I.…”
mentioning
confidence: 99%